Buffer-aided serial relaying for FSO communications - Abou-Rjeily, Chadi (2018)
In this paper, we analyze multi-hop free-space optical (FSO) communications in the context of decode-and-forward serial relaying, where the relays are equipped with finite-size buffers. Based on a Markov chain analysis, we derive closed-form asymptotic expressions for the system outage probability (OP) and average packet delay (APD) for an arbitrary number of relays N, and an arbitrary buffer size L. The closed-form evaluation links the system performance to the various network parameters in a simple and intuitive manner, and it is useful for offering clear insight on the impact of the relay placement and the selection of the buffer size for practical FSO systems. We prove that buffer-aided multi-hop systems can reap a diversity gain that ranges from [(N τ /2)] + 1 to N τ + 1 compared with multi-hop buffer-free systems while the asymptotic APD values can range from N τ to (L - 1)N τ for L ≥ 2. Our analysis also highlights the optimal solutions capable of concurrently minimizing the OP and APD.